2023
DOI: 10.1161/circresaha.122.321762
|View full text |Cite
|
Sign up to set email alerts
|

Hypertension as Cardiovascular Risk Factor in Chronic Kidney Disease

Abstract: Hypertension is the leading modifiable cause of premature death and hence one of the global targets of World Health Organization for prevention. Hypertension also affects the great majority of patients with chronic kidney disease (CKD). Both hypertension and CKD are intrinsically related, as hypertension is a strong determinant of worse renal and cardiovascular outcomes and renal function decline aggravates hypertension. This bidirectional relationship is well documented by the high prevalence of hypertension … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(30 citation statements)
references
References 145 publications
1
19
0
Order By: Relevance
“…Through LASSO regression analysis, we identified a positive association between Na and CKD, even after adjusting for covariates such as general characteristics and routine blood markers. This aligns with the results of a retrospective cohort study ( 16 ), possibly because excessive Na intake can elevate blood pressure, a known risk factor for CKD ( 17 ). However, it has also been observed that both low and high concentrations of Na ion are associated with increased mortality risk in CKD patients ( 18 ).…”
Section: Discussionsupporting
confidence: 84%
“…Through LASSO regression analysis, we identified a positive association between Na and CKD, even after adjusting for covariates such as general characteristics and routine blood markers. This aligns with the results of a retrospective cohort study ( 16 ), possibly because excessive Na intake can elevate blood pressure, a known risk factor for CKD ( 17 ). However, it has also been observed that both low and high concentrations of Na ion are associated with increased mortality risk in CKD patients ( 18 ).…”
Section: Discussionsupporting
confidence: 84%
“…However, when hypertension exists, this risk could be higher. It seems that patients with chronic kidney disease presents higher rates of uncontrolled hypertension when evaluated with ABPM, compared with OBPM, as well as high rates of masked hypertension and nondipping status during sleep, conditions further related with poor cardiovascular outcomes [53,54]. Hence, BP evaluation and control could not be relied only on OBPM in hypertensive individuals with chronic kidney disease.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we selected diabetes and dyslipidaemia as comorbidities, which are cofactors of cardiovascular disease, cerebrovascular disease and hypertensive nephropathy. [25][26][27] These two types of disease could affect the incidence of hypertensive complications.…”
Section: Discussionmentioning
confidence: 99%